Laboratory manual for electrical machines - Kothari, D. P.; Umre, B. S. (New Delhi : I. K. International Pub. House Pvt. Ltd., 2013)
Provides the basic information to students of the machine phenomenon, working principles and testing methods. It also offers an understanding of various types of electrical machines. This laboratory manual includes power point presentations for all experiments. The conclusion at the end of each experiment explains the behavior of various machines.
Exp 1. To Study the Speed Control of a DC Shunt Motor by (a) varying armature voltage with field current kept constant. (b) Varying field current with armature voltage kept constant; Exp 2. To Perform Load Test on a DC Shunt Generator; Exp 3. To Perform Open Circuit and Short Circuit Test on a Single-Phase Transformer; Exp 4. To Study (a) the Polarity Markings on Single-Phase Transformer Windings and (b) the Operation of an Autotransformer; Exp 5. To Study the Load Test on a Cumulatively Compounded DC Motor; Exp 6. To Study the Load Test on a Three-Phase Induction Motor; Exp 7. To Determine Voltage Regulation and Efficiency of a Single-Phase Transformer by Direct Loading; Exp 8. To Study the Scott-Connection of Transformers (Three-Phase to Two-Phase Conversion); Exp 9. To Study the Variation of Speed and Load Test on Schrage Motor; Exp 10. To Plot V and Inverted V ([LAMBDA]) Curves of a Synchronous Motor; Exp 11. To Determine the Ratio Xq/Xd for Three-Phase Alternator by using "Slip Test"; Exp 12. To Study the Synchronization of an Alternator with an Infinite Bus by "Dark Lamp Method"; Exp 13. To Determine Potier Reactance of Three-Phase Alternator by "Zero Power Factor Lagging Saturation Curve"; Exp 14. To Determine Negative Sequence and Zero Sequence Reactance's of Synchronous Generator; Exp 15. To Study the Characteristics of Three-Phase Induction Generator; Exp 16. To Determine Direct Axis Sub transient (Xd"), Quadrature Axis Sub transient (Xq") Reactance's of Synchronous Machine.
Includes bibliographies and index.
Keywords: Electric machinery